Tunable and sustained-release characteristics of venlafaxine hydrochloride from chitosan-carbomer matrix tablets based on in situ formed polyelectrolyte complex film coating - Xiaofei Zhang; Xiangqin Gu; Xiaodan Wang; Huimin Wang; Shirui Mao (Elsevier, 2018)
The objective of this study is to design sustained-release tablets using matrix technology, which can well control the release of highly water-soluble drugs with good system robustness and simple preparation process. Taking venlafaxine hydrochloride (VH) as a drug model, the feasibility of using chitosan (CS), carbomer (CBM) combination system to achieve this goal was studied. Formulation and process variables influencing drug release from CS-CBM matrix tablets were investigated. It was found that CS-CBM combination system weakened the potential influence of CS, CBM material properties and gastric emptying time on drug release profile. Demonstrated by direct observation, differential scanning calorimetry (DSC) and Fourier transform infrared spectroscopy (FTIR), in situ self-assembled polyelectrolyte complex (PEC) film was formed on the tablet surface during gastrointestinal tract transition, which contributed to the tunable and robust control of drug release. The sustained drug release behavior was further demonstrated in vivo in Beagle dogs, with level A in vitro and in vivo correlation (IVIVC) established successfully. In conclusion, CS-CBM matrix tablets are promising system to tune and control the release of highly water-soluble drugs with good system robustness. Keywords: Venlafaxine hydrochloride, Polyelectrolyte complex, Sustained-release, Robustness, Pharmacokinetic